EFFECT OF EYESTALK ABLATION IN THE SPINY LOBSTER PANULIRUS HOMARUS (LINNAEUS): 3. ON GONADAL MATURITY - Radhakrishnan, E V; Vijayakumaran, M (Indian Journal of Fisheries, 2011)
Eye ablation induced accelerated gonadal growth in males and females,indicating gonad inhibiting principles in the eyestalk. Eyestalk removal resulted in'pink haeraolympii' in maturing and mature females and also inhibited the developmentof secondary sexual characters in them. The normal antagonistic relationshipof moulting and reproduction was changed to one of synergism in ablated lobsters.Ablation of eyestalks initiates relatively strong moulting tendency than reproductionin P. homarus.